Assessing the Impact of Solar PV and Li-Ion Battery Learning Rate on Power Sector Decarbonization in Indonesia - Reyseliani, Nadhilah; Primayuda, Stephanus; Salim, Inggarjati Qolbun (Riviera Publishing, 2025)
Power sector decarbonization requires assessing the competitiveness of renewable energy, particularly solar PV, against fossil fuels. However, the literature reveals significant variability in projected solar PV cost reductions, which are also influenced by lithium-ion battery costs. This study aims to examine the effects of varying solar PV and Li-ion battery learning rate scenarios on Indonesia's power system planning through 2060, investigating economic competitiveness, emissions reduction, investment patterns, and electricity production costs. Therefore, using a learning curve approach within the TIMES optimization model, this study examined three scenarios (A: pessimistic, B: moderate, C: optimistic) of solar PV and battery cost reductions on Indonesia's power system through 2060 under the least-cost basis (BAU) and with coal phase-out planning (BAU PO). The results show that in BAU-C, it accelerates solar PV competitiveness by 5–10 years and reduces cumulative emissions by 15.7% (vs. 4.3% in BAU-B) but accumulates investment in the last decade. In BAU PO, the difference in learning rate does not alter the adoption year of solar PV, but rather the annual mix, resulting in a more even distribution of investment, albeit with a broader range of electricity production costs in 2055–2060. Emissions tend to remain constant, with an annual increase of 0.5–1.2% compared to 2020. This study also assesses the principal reduction in emissions as stemming from the coal phase-out policy, compared to the contributions of solar PV and battery competitiveness. These findings have important implications for energy policy in developing countries, highlighting the dominant role of coal phase-out policies versus technology learning effects in achieving decarbonization goals.